Logistics engineering and management - Blanchard, Benjamin S. (Prentice-Hall international series in industrial and systems engineering., 1998)
For Industrial Engineering courses focusing on logistic engineering and management. An authoritative exploration of logistics management within the engineering design and development process, this book concentrates on the design, sustaining maintenance and support of systems